KOMBINASI IDT-TAM UNTUK ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN APLIKASI PERUSAHAAN - Muhammad Yusril Helmi Setyawan; Harry Khomas Saputra, Mohammad (Jurnal Mnemonic, 2022)
Utilization of information systems or company applications can encourage increased company performance. The involvement of employees in utilizing the application will increase the company's opportunities to carry out its performance. That is marked by the disclosure of the company's operational information so that it is sufficient to help the company's policy makers to determine the right strategy for the company. This study aims to determine the factors that influence employee intentions to the perceived usefulness of company applications. By combining the Innovation Diffusion Theory (IDT) method with the Technology Acceptance Model (TAM), this study proposes an expanded implementation of TAM. This model was tested with data collected from 72 employees from a population of 263 employees in 11 different work units. Structural Equation Modeling (SEM) analysis uses smartPLS to explain the acceptance process. The results show that the model is able to explain the factors that influence employee intentions to use company applications where the innovation factors in IDT can be traced to their influence on the main factors of TAM. The subjective assumption of employees in using applications is lower than objective conditions, meaning that the current use of applications is more driven by social factors that influence behavioral intentions to use applications